Characterization Of Hydrophobic-Treated Recycled Paper Mill Sludge In Bituminous Materials - Tracy, Wong Leh Xin (Universiti Sains Malaysia, 2021)
The increasing amount of solid waste generated and disposal activities due to massive urbanisation has led to limited landfill space. Asphalt pavement industry has seized this opportunity to transform the solid wastes as modifiers into bituminous mixtures while practising a sustainable alternative in asphalt pavement technology. This research implements Recycled Paper Mill Sludge (RPMS) as a solid waste additive to partially replace the mineral filler in asphalt mixture. The raw RPMS required a 24-hour oven drying to completely eliminate its water content, prior to the reduction of size by granulating and grinding the dried RPMS. The 0.075mm and pan size unmodified RPMS are obtained by sieving process in which those retained on 75μm and pan size sieve are collected and kept in an air-tight container for the research usage. The particles of RPMS are determined by particle size distribution test. RPMS is modified by ethanol method which involving an esterification of ethyl esters that utilizing 7ml of waste cooking oil (WCO) and 50ml of ethanol. This treatment method yielded modified RPMS with improved hydrophobicity which resulted in a lower hydrophilic coefficient and higher water contact angle than the unmodified RPMS. From Scanning Electron Microscope (SEM), it illustrated the modified RPMS with less fibrous components, rough and porous surface texture, agglomeration of particles and regular shapes. The RPMS is incorporated into asphalt mixtures at 0.5% and 1.0% of the weight of aggregates. In this research, asphalt binder of 60/70 and granite aggregates are used. The asphalt mixture is mixed and compacted at temperatures of 160℃ and 150℃ respectively. Both modified asphalt mixtures achieved an increased optimum binder content (OBC). The adsorption strength is proved to be stronger for modified RPMS compared to common fillers such as limestone and granite dust from baghouse. Mechanical properties for instances stability, flow and stiffness of modified asphalt mixtures are determined from Marshall Stability test. The results showed that the three properties decreased with the incorporation of modified RPMS. Despite that, the results are within the Public Work Department (PWD) requirement range and hence the incorporation of RPMS is applicable. Toxicity Characterization Leaching Procedure (TCLP) has proven that only Zinc (Zn), Copper (Cu) and Cadmium (Cd) has found to be exceeded the safe regulatory limits in Malaysia. However, Zn and Cu are excluded from the list of restricted hazardous substances and being the fundamental components for living things and microorganisms. This research implies the implementation of RPMS in asphalt mixture is providing a sustainable technology and greener disposal replacement in asphalt paving industry.